John Steinbeck in Kiev. - Unknown:::Creator::::::::::::
John Steinbeck in Kiev, USSR. Behind and to the right of Steinbeck is Russian translator Frida Lurie. Ukrainian playwright and the head of Ukrainian Soviet Writers Union Aleksandr Korneichuk is on Steinbeck's right, and Wanda Wassalensky, a Polish and Soviet novelist and journalist, is on Steinbeck's left. Original is in the safe.